SPORT AND LEISURE TRANSFORMING LIVES: THE REALITY OF ANAPOLIS - Oliveira-Silva, Iranse (International Journal of Movement Science and Rehabilitation, 2019)
O ESPORTE E O LAZER TRANSFORMANDO VIDAS: A REALIDADE DE ANÃPOLIS